Motivational factors and changes in master's degree in accounting: the two sides of the same story - Alison Martins Meurer; Antônio Nadson Mascarenhas Souza; Flaviano Costa (Revista Contemporânea de Contabilidade, 2019)
The admission on masters brings relevant modifications in the life of the students, in social, financial or psychological areas. The alteration of reality in the face of new commitments can have some consequences for students, and compromise their performance in the course. In this sense, this research sought to identify how changes (social, financial and psychological) occurred in the lives of students of the master's degree in accounting after joining the postgraduate program. Under the theoretical lens of Human Capital and Self-Determination theories were identified the motivations that fostered the participants' desire for and decision to enter the masters in accounting. To collect the evidences, we conducted semi-structured interviews and applied questionnaires in 12 Brazilian public higher education students. The interview script was submitted to the validations proposed by the specialized literature, and the ethical aspects were observed by the researchers. Based on the analysis of participants' speeches and possible knowledge, it is necessary to inform the coordination of Brazilian postgraduate courses, the development agencies, teachers, students and future candidates. First, the results point in all aspects, active and financial, there were modifications in the lives of the majority of participants. The speeches indicate that the financial factor is considered one of the most important and observed by the masters for the completion of the course. In addition, an overload of activities and a lack of planning both in relation to the time and financial aspects, psychologically impact the students. It was also noticed that motivations that led the students to enter the postgraduate program are aligned with professional goals, but are also strongly related to personal satisfaction and other intrinsic motivations. Thus, it is considered that the study gave voice to the masters, as it innovates for its qualitative character and in-depth analysis. Finally, this research is a reflection of the portrait and design of the postgraduate course in Brazil. It is hoped that the findings will serve as a basis for maintained and improved student maintenance policies, as well as the design of Brazilian postgraduate studies.